2003
DOI: 10.1016/s0093-934x(02)00556-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of phonological and orthographic information in lexical selection

Abstract: We report the performance of two patients with lexico-semantic deficits following left MCA CVA. Both patients produce similar numbers of semantic paraphasias in naming tasks, but presented one crucial difference: grapheme-to-phoneme and phoneme-to-grapheme conversion procedures were available only to one of them. We investigated the impact of this availability on the process of lexical selection during word production. The patient for whom conversion procedures were not operational produced semantic errors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Relatedly, Miceli et al (1999) showed that semantic errors of aphasic patients could influenced by recently produced words in the same (oral) or different (written) modality. This finding indicates that word retrieval processes may be constrained by previously activated form information (phonological or orthographical; see also Alario et al, 2003). Further evidence for the influence of phonological properties on word retrieval comes from priming studies (Ferreira & Griffin, 2003; see also Jaeger et al, 2012, andSamuel, 2002).…”
Section: Phonological Influences On Word Retrieval During Language Prmentioning
confidence: 85%
“…Relatedly, Miceli et al (1999) showed that semantic errors of aphasic patients could influenced by recently produced words in the same (oral) or different (written) modality. This finding indicates that word retrieval processes may be constrained by previously activated form information (phonological or orthographical; see also Alario et al, 2003). Further evidence for the influence of phonological properties on word retrieval comes from priming studies (Ferreira & Griffin, 2003; see also Jaeger et al, 2012, andSamuel, 2002).…”
Section: Phonological Influences On Word Retrieval During Language Prmentioning
confidence: 85%
“…Production models that include lemmas have most often been constructed to account for speech production. However, the assumptions they make can be extended to include an account of written production (see discussions in Alario, Schiller, Domoto-Reilly, & Caramazza, 2003;Berndt & Haendiges, 2000). In such an extended model the lemma is connected to two lexemes, one in the phonological lexicon and one in the orthographic lexicon.…”
Section: The Relationship Between Oral and Written Productionmentioning
confidence: 99%
“…A consequence of this is that models of lexical access would not need to postulate an intermediate lexical level of lemmas. This is because the lemma level is, among other things, intended to represent grammatical information separated from modalityspecific information (Caramazza, 1997;Roelofs, Meyer, & Levelt, 1998, defend the alternative view that grammatical class deficits restricted to one modality of output are due to an access impairment; in this interpretation difficulties in accessing the forms of words of certain grammatical categories would be the consequence of a deficit in the transmission of information from the lemmas of certain grammatical categories to the corresponding lexemes; see discussion in Alario et al, 2003).…”
Section: Cognitive Neuropsychology 2004 21 (8) 809mentioning
confidence: 99%
“…Phonological analysis includes grapheme-to-phoneme conversion (Berndt et al, 1994), decoding and retrieval of sound forms of the written words (Herbster et al, 1997;Fiez et al, 1999;Walter et al, 2001;Alario et al, 2003;Simon et al, 2006). Manipulating phonemes and phonological forms of the words involves the superior temporal gyrus (BA 22) (Pugh et al, 1996;Vandenberghe et al, 1996;Lurito et al, 2000;Billingsley et al, 2001;Vigneau et al, 2006) and the inferior frontal gyrus (pars triangularis and opercularis; BA 44, 45) (Zatorre et al, 1992;Dapretto and Bookheimer, 1999;McDermott et al, 2003;Seghier et al, 2004).…”
Section: Introductionmentioning
confidence: 99%